2018
DOI: 10.3389/fphys.2018.00978
|View full text |Cite
|
Sign up to set email alerts
|

Following a Long-Distance Classical Race the Whole-Body Kinematics of Double Poling by Elite Cross-Country Skiers Are Altered

Abstract: Introduction: Although short-term (approximately 10-min) fatiguing DP has been reported not to alter the joint kinematics or displacement of the centre of mass (COM) of high-level skiers, we hypothesize that prolonged DP does change these kinematics, since muscular strength is impaired following endurance events lasting longer than 2 h.Methods: During the 58-km Marcialonga race in 2017, the fastest 15 male skiers were videofilmed (100 fps, FHD resolution in the sagittal plane) on two 20-m sections (inclines: 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Specifically, these MIT sessions were performed using DP, either with long intervals (8–15 min) with short breaks (1–2 min) or as continuous 45- to 75-min sessions. Such sessions aim to delay the duration-related fatigue of long-distance races, which leads to reduced coordination, and this directly or indirectly affects the ability to maintain muscle power throughout the competition (Zoppirolli et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, these MIT sessions were performed using DP, either with long intervals (8–15 min) with short breaks (1–2 min) or as continuous 45- to 75-min sessions. Such sessions aim to delay the duration-related fatigue of long-distance races, which leads to reduced coordination, and this directly or indirectly affects the ability to maintain muscle power throughout the competition (Zoppirolli et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the Olympic disciplines include the use of and transition between many different subtechniques (Sandbakk and Holmberg, 2017 ; Solli et al, 2018 , 2020 ), the relatively flat terrain profiles in long-distance events are often won on skis without grip wax, using solely the double-poling (DP) subtechnique (Sagelv et al, 2018 ; Zoppirolli et al, 2018 , 2020 ; Skattebo et al, 2019 ; Stöggl et al, 2020 ) As a consequence of these demands and the increasing popularity of long-distance XC skiing, such as the Visma Ski Classics (VSC) series, long-distance XC skiers have fully specialized their training for performance in long-distance events (Skattebo et al, 2019 ). However, in contrast to the detailed examinations of physiological profiles and training characteristics of Olympic XC skiers (Sandbakk et al, 2011 , 2016 ; Tønnessen et al, 2014 ; Sandbakk and Holmberg, 2017 ; Solli et al, 2017 ), these factors have been almost unexplored among skiers who have specialized in long-distance XC.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, the DP technique has been extensively analyzed, with studies focusing on different inclines, 6 poling frequencies, 7 subgroups of athletes, 8 and kinematic changes during a race. 9 However, to our knowledge, studies investigating the physiology and the technique of DP specialists are lacking. The only study to date found lower submaximal O 2 cost and blood lactate concentrations ([La -]) in DP and equal VO 2 peak in both DP and diagonal skiing in elite long-distance skiers compared with all-round skiers.…”
mentioning
confidence: 99%
“…To date, 2-D video recordings have been most commonly employed for kinematic analysis. As long as certain conditions are met, the reliability of such data is comparable to that collected in the laboratory with more advanced optoelectronic motion capture systems [59].…”
Section: Video Camerasmentioning
confidence: 80%
“…Calibration requires filming (in the plane of the skier´s movements) a frame (or set of objects) whose dimension (or distance) is as large as possible and precisely known. With multiple skiing lanes, each lane should be calibrated individually [59].…”
Section: Video Camerasmentioning
confidence: 99%